STUDI PENDAHULUAN PENGGUNAAN ZPT CAMPURAN UNTUK INVIGORASI BENIH KAKAO (Theobroma cacao L.) SETELAH DISIMPAN - Nurhayati Nurhayati; Tardi Kurniawan; Sarwendah Ratnawati Hermanto (Journal of Agro Plantation (JAP), 2025)
One way to increase the vigor (invigoration) of cocoa seeds after storage is by soaking them in a solution containing plant growth regulators (PGRs). This study aimed to determine the effect of a mixture of shallots, aloe vera, and betel leaves on the vigor of cocoa seeds after 28 days of storage. The study was conducted at the Quality 2 Laboratory, the Microbiology Laboratory of Ketapang State Polytechnic, and the Experimental Field in Suka Bangun Village from February to April 2025. This study used a Completely Randomized Design (CRD) with 4 treatments and 5 replications. Each replication consisted of 20 seed samples. The treatments consisted of: P0: Aquades (without mixed plant growth regulators), P1: 60% mixed plant growth regulators, P2: 40% mixed plant growth regulators, and P3: 20% mixed plant growth regulators. The parameters observed were water content, moldy seedling growth during seedbed, and seed germination during seedbed. Data were analyzed using variance analysis and DMRT test was conducted at the 5% level. The results obtained in the study showed that the application of a mixture of plant growth regulators (PGR) of shallots, aloe vera, and betel leaves was not able to increase cocoa seeds vigor after 28 days of storage.